Optimalisasi Kemahiran Qira'ah Melalui Daurah Nahwiyah Digital Berbasis Teknologi Interaktif Bagi Mahasiswa PBA UNM - Raudatussolihah, Baiq; Fathurrahman, Ali; Rais. TM., Ahmad; Laila, Hikmatul; Kholida, Masita Taufiqi (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2025)
Qira'ah ability (reading Arabic text) is a basic competency for students of the Arabic Language Education (PBA) study program at Makassar State University (UNM). However, the limitations of conventional learning methods often hinder the improvement of this ability. Therefore, this study aims to optimize qira'ah ability through the Daurah Nahwiyah Digital program based on interactive technology. This study uses qualitative methods through observation, interviews and documentation. The results of the study indicate that the use of interactive technology in Daurah Nahwiyah Digital is effective in improving students' understanding of nahwu rules and improving reading skills. Thus, the integration of technology in qira'ah learning can be a solution in improving the competence of PBA UNM students in understanding and reading Arabic texts.